Performing Readiness-to-Scale Analysis of Healthy Diet Innovations in West, Central and East Africa - Ndindeng,S.A.; Nwilene, F.; Bah, S.; Twine, E.; Tang, E.; Savadogo, E.; Tchatcha, D.; Ndungu, J.; Kittika, M.; Faye, F.; Dembele, A.; Konan, G. (2025)
Activity 2.3.4.1 focused on conducting a systematic readiness-to-scale analysis of some healthy diet innovations developed and tested across West, Central and East Africa under HealthyDiets4Africa (HD4A), and informed by complementary experience from TAAT-II, Seeds4Liberia, and RIZAO. The activity addressed a critical scaling gap: while numerous nutrition-sensitive and rice-based innovations exist, evidence on their maturity, actual use, and readiness for expansion has often been fragmented or absent, limiting strategic scaling and investment decisions. Using the CGIAR Scaling Readiness framework, AfricaRice led the identification, documentation, and assessment of 55 healthy diet innovation packages, covering products, technologies, processes, and services across production, processing, marketing, and consumption. Each innovation was assessed against two standardized dimensions—Innovation Readiness Level (IRL) and Innovation Use Level (IUL)—to generate an objective picture of technical maturity and real-world deployment. The analysis revealed that while 32 innovations have reached medium to high readiness levels (IRL ≥5), 33 innovations remain at low levels of use, indicating a significant readiness–use gap. Only 11 innovations demonstrated both high readiness and high use, identifying them as immediately scale-ready, while others require targeted delivery, business model, or policy support before broader scaling. Overall, Activity 2.3.4.1 generated a validated evidence base to guide intentional, sequenced scaling of healthy diet innovations, strengthen alignment with CGIAR Scaling for Impact (S4I) principles, and inform future investment under TAAT-III, REWARD, national programs, and donor-supported initiatives. The readiness dataset also provides a living monitoring tool to track progress along scaling pathways over time